Semantics of the Russian and Polish adjectives containing the глуп- / głup- root - Walczak, Maciej (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The author performs a comparative analysis of the meanings of the Russian and Polish adjectives containing the глуп- / głup- root. The analysis also considers their word-formative features. The underlying material was sourced from the contemporary and historical explanatory dictionaries as well as etymological dictionaries and dictionaries of dialectal and old lexis. This analysis made it possible to observe that the Polish units have a stronger word-formative potential, especially with regard to derivatives with suffixes of subjective assessment. Depending on the context, these derivatives may introduce diminutive and augmentative meanings and mainly refer to the archaic store of the Polish language. The strongest semantic differences between the two languages can be observed among dialectal units.